Paradigma Manajemen Pendidikan Pada Badan Diklat Dalam Penerapan Good Government - Fetrimen Fetrimen (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2018)
In implementing Good Government, the government has an agenda for the realization of community welfare: first, the political agenda; second, the legal agenda. This study aims to find out how the structure of the implementation of good government is implemented by stakeholders after getting education and training with an education management approach. This study applies a qualitative method through content analysis. The implementation of the government agenda can be realized by changing the education management paradigm in the government-owned Education and Training Agency so that the principle of legal certainty, orderly state administrators, public interest, openness, proportionality, professionalism, accountability, efficiency and principles of effectiveness in accordance with article 20 paragraph 1 Law Number 32 of 2004 concerning Regional Government can be increased. Efforts that can be made through the implementation of education management: (a) decentralization of education in the Education and Training Agency, (b) community-based education, (c) school-based management, (d) Education and Training Agency based on quality improvement, (e) Agency Competency Curriculum-based Education and Training, (f) Skills-based education, (g) Contextual learning, (h) Authenticity-based assessment.